2010
DOI: 10.1093/intqhc/mzq016
|View full text |Cite
|
Sign up to set email alerts
|

Reducing inappropriate diagnostic practice through education and decision support

Abstract: The reduction was significant but inappropriate practice was not eliminated. For as long as decision-support systems are 'stand-alone' applications, achieving full compliance is dependent on continuous and expensive processes of education and enforcement. A better understanding of why clinicians fail to follow recommended practice is required, and decision support must be better embedded into clinical workflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…However, a seminal study conducted by Brenner and Hall (13) warns against its bad effects (particularly for children) due to the radiation exposure associated with CT. Independent CT imaging studies (12, 14, 15) advocate the adoption of a comprehensive approach that targets physicians’ education to decrease the over-reliance on CT imaging for those suffering from brain disease. Therefore, to reduce the harmfulness of CT, it can be beneficial to use data mining methods specially, NBN as a predictor.…”
Section: Resultsmentioning
confidence: 99%
“…However, a seminal study conducted by Brenner and Hall (13) warns against its bad effects (particularly for children) due to the radiation exposure associated with CT. Independent CT imaging studies (12, 14, 15) advocate the adoption of a comprehensive approach that targets physicians’ education to decrease the over-reliance on CT imaging for those suffering from brain disease. Therefore, to reduce the harmfulness of CT, it can be beneficial to use data mining methods specially, NBN as a predictor.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have found as much as 30% of all imaging tests are inappropriate in some fashion [3840]. In some instances no imaging test is warranted at all, but more often are the situations where an alternative modality could have been utilised with lower or no radiation burden such as ultrasound, a plain radiograph or, MRI imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features of VTE are variable; many patients remain asymptomatic, while others present with non‐specific illness, for which further investigation is required, particularly when pulmonary embolism (PE) is suspected. Diagnostic management of patients with suspected VTE is often inappropriate and does not always conform to recommended guidelines 1 , 2 . The use of structured diagnostic algorithms and decision‐support tools improves the accuracy of clinical assessment and the appropriateness of referral of patients with suspected VTE; however, these resources are seldom used by referring clinicians, in spite of evidence that adherence to guidelines significantly improves clinical outcomes 1 .…”
mentioning
confidence: 99%
“…Such structured assessment has now become standard practice in Western Australian teaching hospital emergency departments, where an online decision‐support tool has been available since 2001 1 , 6 . There is a widespread perception among imaging specialists in public hospitals in WA that, in spite of the availability of structured assessments and decision support, the volume of referrals for VTE investigations has increased over recent years, and that many may be inappropriate 2 . We aimed to document trends in referrals for VTE‐related imaging within WA teaching hospitals to see whether this perception is valid and what impact any increase in testing may have had on the incidence of deaths related to PE.…”
mentioning
confidence: 99%